Fungi associated with dry rot disease of yam (Dioscorea rotundata Poir.) tubers in Cordoba, Colombia - Arrieta-Guerra, Jhony José; Díaz-Cabadiaz, Abelardo Tulio; Pérez-Pozos, Jazmín Vanessa; Cadena-Torres, Jorge; Sánchez-López, Diana Beatriz (Agronomía Mesoamericana, 2021)
Introduction. Dry rot is a disease that has acquired great importance in Colombia because it causes losses in yam (Dioscorea rotunda Poir.) tubers, both in the field and in postharvest, affecting the economic income and productivity of smallholders. Information on the causal agents of this disease is scarce, so the strategies for managing this problem are unclear. Objective. To identify and characterize fungi associated with the dry rot disease of yam tubers. Materials and methods. This research was carried out between March and October 2019, in the coastal zone of the Córdoba department in the Colombian Caribbean. Yam tubers were collected in storage, due to the fact that farmers keep them as seeds for future harvests. In the laboratory, the associated fungi was isolated from the lesions, characterized, and then identified through the amplification of the ITS (Internal Transcribed Spacer) region of the ribosomal DNA. Results. Twenty-eight fungal growths associated with dry rot of yam tubers were isolated and grouped into eleven morphotypes of which ten species were identified, belonging to nine fungal genera. Conclusion. Six fungi could be associated with the dry rot of yam tubers in the coastal zone of Colombia. These would be: Lasiodiplodia theobromae, Fusarium solani, Rhizopus oryzae, Neocosmospora rubicola, Neoscytalidium dimidiatum, and Curvularia aeria.